T-cell engagement of dendritic cells rapidly rearranges MHC class II transport - Boes, Marianne; Cerny, Jan; Massol, Ramiro; Op den Brouw, Marjolein; Kirchhausen, Tom; Chen, Jianzhu; Ploegh, Hidde L. (Nature (London), 2002)
Assembly of major histocompatibility complex (MHC) molecules, which present antigen in the form of short peptides to T lymphocytes, occurs in the endoplasmic reticulum; once assembled, these molecules travel from the endoplasmic reticulum to their final destination. MHC class II molecules follow a route that takes them by means of the endocytic pathway, where they acquire peptide, to the cell surface 1 . The transport of MHC class II molecules in ‘professional’ antigen-presenting cells (APCs) is subject to tight control and responds to inflammatory stimuli such as lipopolysaccharide. To study class II transport in live APCs, we replaced the mouse MHC class II gene with a version that codes for a class II molecule tagged with enhanced green fluorescent protein (EGFP). The resulting mice are immunologically indistinguishable from wild type. In bone-marrow-derived dendritic cells, we observed class II molecules in late endocytic structures with transport patterns similar to those in Langerhans cells observed in situ . We show that tubular endosomes extend intracellularly and polarize towards the interacting T cell, but only when antigen-laden dendritic cells encounter T cells of the appropriate specificity. We propose that such tubulation serves to facilitate the ensuing T-cell response.